Purchase price of independently produced power : the case of Nepal - Thapa, Raj Kumar; Shrestha, Ram M.; Chen, Xavier; Giap, Van Dang; Saeed, Khalid; Government of Japan; Asian Development Bank (Bangkok : Asian Institute of Technology, 1995)
Independent Power Producers (IPPs) are a major source of new power generation capacity both in the industrialized and developing countries. They have a potential to meet large and immediate financing gap by mobilizing direct foreign investment in the power sector. In developing countries IPPs have tapped new forms of financing in international capital markets. Private sector involvement in the power sector has also led to impressive construction and operational efficiency gains. Properly structured IPPs can also stimulate the development of local capital markets. The study undertakes several detailed system expansion plans for the hydro dominated electricity supply sector of Nepal for the period 1996-2015. Wein Automatic System Expansion Planning Model developed by the International Atomic Energy Agency has been used to carryout the system expansion plan with and without the contribution of the IPP. Significant costs of up to 20% of the total cost in the planning horizon was found to be avoided by the utility as a consequence of IPP supply to the grid. A voided costs have been calculated from the long-run marginal cost perspective and adjusted for financial requirements. The avoided costs of 5.05 cents/kWh were found to be 6.48% lower than that required, 5.40 cents/kWh, to provide the required rate of return on equity of 16%, for the IPP under consideration.
A thesis submitted in partial fulfillment of the requirement for the degree of Masters of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Electric utilities -- Nepal -- Costs